Types and frequency of malignant abdominal tumors in childhood - Chizzola, Manlio; Añón, Ruben (Cirugía del Uruguay, 1972)
Seventy-fiv.e cases of malignant abdominal tumors in children, treated in the Services of the Ministry of Public Health over a ten-year period -1961-70- are analyzed. 'The different typ.es (intra-, sub-, and retroperitoneal) are considered and their respective frequency is noted. Special consideration is given to variety and frequency ,within these types: varieties are classified, frequence is registered and clinical, laboratory and. radiological methods for establishing diagnosis are discussed. The paper includes data on the .evolution of each variety and on the treatment applied.